MODEL PRODUKTIVITAS BAGI HASIL AGROINDUSTRI GULA TEBU DALAM KEMITRAAN ANTARA PETANI DAN PERUSAHAAN: STUDI KASUS DI PG KREMBOONG, SIDOARJO - Wahyu Kanti Dwi Cahyani, Marimin, dan Sukardi (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
In the agricultural activity especially sugarcane industries, there was untrust issue between farmers and sugarcane industry on yield measurement that impacting onfarmers’ performance and income. The objective of this study was to formulate gainsharing productivity, with the following steps: 1) analyzed factors influencing the crops yield, 2) created a model for yield prediction, 3) constructed a model of gainsharing productivity, 4) analyzed the institutional to increase gainsharing productivity and 5) established recommendation strategy for gainsharing productivity. System thinking, multiple linear regression (SPSS) and production function research, ISM and SWOT-AHP were used as an approach and technique. Face validation from expert judgment was used for verification and validation. The result showed that sugarcane quality, brix, and pol analyzing gave a huge impact on crops yield. Yield prediction model generated 7.17% and r2 100%. The second scenario of model (66:34 yield <6%; 70:30 yield 6.01%-7.00%, 72.5:27.5 yield 7.01%-8.00% and 75:25yield >8.01%) and cash & carry scheme were selected for the gainsharing model among farmers and sugarcane industry. Institutional partnership model generated one sub of the objective key element, two subs of the constraint key element, four subs of the requirement key element and one sub of the actor key element. The selected strategy for gainsharing productivity was the integration of sugarcane plantation with sugarcane industry with value 0.170 and cash & carry with value 0.116.Keywords: gainsharing productivity (scanlon plan), institutional partnership, sugarcane agroindustry